Role-play in Literature Lectures: the Students’ Assessment of their Learning. - Isobel Ryan; Ciarán Dawson; Marian McCarthy (International Journal for the Scholarship of Teaching and Learning, 2018)
The following article is based on a piece of qualitative research on the use of role-play in a literature module in the Modern Irish Dept. of University College Cork in 2015. There were 18 students involved in the research. The aim of the research was to establish what value students associate with the use of role-play in literature lectures. Role-play is used widely in language classes but less widely in literature lectures. Classroom Assessment Techniques (CATs); questionnaires; a focus group; and essays were used as a means of gathering data. The research findings indicate that students are nervous when first presented with the prospect of doing role-play in class; however, the findings show that these feelings soon give way to a happy acceptance of role-play and an appreciation of this teaching methodology as beneficial to both teaching and learning. The students who took part in the study were very enthusiastic about the group work involved in preparing and performing role-play. While the author recognises that role-play may not lend itself to all teaching contexts, she wishes to encourage other literature teachers to experiment with role-play.